Microstructured scaffold for guided cellular orientation: Poly(ε-caprolactone) electrospinning on laser ablated titanium collector. (November 2017) - Ginestra, P.S.; Pandini, S.; Fiorentino, A.; Benzoni, P.; Dell'Era, P.; Ceretti, E.
Abstract: Many processes have been considered for fabricating scaffolds including additive manufacturing, electrodeposition and electrospinning. Among them, electrospinning is gaining attention because of its simplicity and the possibility to realize nano-scale fibers in a wide range of materials. In this paper, micro-structures were laser ablated on titanium collectors for the electrospinning process to obtain micro-patterned scaffolds. The results show the capability and the precision of the process in replicating the micro-scale features by electrospinning technology. Moreover, L6 rat myoblasts were seeded on different patterned scaffolds and results show how it is possible to control cells orientation by choosing the proper micro-pattern.